(untitled) (Iraqi National Journal of Earth Science (INJES), 2026)
The upper Jurassic Naokelekan Formation has been investigated using X-ray diffraction and scanning electron microscopy in two outcrop sections from Halabja and Barzinja areas in northeastern Iraq to determine mineralogical composition. The study shows that abundance of calcite, rare dolomite, quartz, feldspars and some other minerals such as pyrite, goethite, natrolite and apatite form the main non-clay composition. Illite (mica) and mixed layers of illiteare the clay minerals. Calcite is the dominant mineral in all the studied samples while the presence of the framework silicates of quartz and feldspars (plagioclase and K-feldspar) shows a variation across the studied sections, where they increase in the argillaceous limestone and calcareous shale samples. Various forms of calcite reflect contribution from depositional environment, diagenesis, inorganic mineralization and biogenic contribution, while detrital contribution due to weathering is responsible for the quartz and some feldspar content. Hot arid paleoclimatic conditions is indicated by common presence of illite (mica).